2014
DOI: 10.1007/978-1-4471-6338-1
|View full text |Cite
|
Sign up to set email alerts
|

An Anthology of Theories and Models of Design

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 213 publications
0
11
0
Order By: Relevance
“…They are being taught today in different countries (e.g., France, Sweden, US, UK, Israel, Tunisia, Japan) in various contexts: engineering schools, management schools, business schools, design curricula, entrepreneurship schools, and universities. The impact of these educational practices has been reported in several studies Dym et al 2005;Hatchuel et al 2011b;Nagel et al 2016); Recent experiments based on a cognitive perspective have shown that theoretically grounded approach to teaching, significantly increases the capacity of students to resist fixation (Agogué and Cassotti 2012).…”
Section: Conclusion: Design Theory -Enabling Further Researchmentioning
confidence: 97%
“…They are being taught today in different countries (e.g., France, Sweden, US, UK, Israel, Tunisia, Japan) in various contexts: engineering schools, management schools, business schools, design curricula, entrepreneurship schools, and universities. The impact of these educational practices has been reported in several studies Dym et al 2005;Hatchuel et al 2011b;Nagel et al 2016); Recent experiments based on a cognitive perspective have shown that theoretically grounded approach to teaching, significantly increases the capacity of students to resist fixation (Agogué and Cassotti 2012).…”
Section: Conclusion: Design Theory -Enabling Further Researchmentioning
confidence: 97%
“…• Axiomatic Design of Nam P. Suh (1990Suh ( , 2001 A good overview over most of the mentioned approaches is presented in Chakrabarti & Blessing (2014). In this book, the role of theories, models and methodologies in Design Science is also discussed in a more general manner.…”
Section: /73mentioning
confidence: 99%
“…On the other hand, the concept space consists of design concept propositions that are at least partially uncertain, i.e., the proposition has no logical status in the knowledge space. In both spaces, propositions build up and depend on each other so that the spaces expand during development as new design concepts evolve in the concept space (new design ideas) and insights are gained in the knowledge space (validated learning) (Hatchuel and Weil, 2003;Agogué and Kazakçi, 2014). (Agogué and Kazakçi, 2014) As visualized in Figure 1, the CK-Theory allows design explorations to different directions (C → C) and an advancement by logical reasoning within the knowledge space (K → K), but fosters reflection to the knowledge base (C → K) which again stimulates new design concept (K → C) propositions (Agogué and Kazakçi, 2014).…”
Section: Ck-theory and Set-based Designmentioning
confidence: 99%
“…In both spaces, propositions build up and depend on each other so that the spaces expand during development as new design concepts evolve in the concept space (new design ideas) and insights are gained in the knowledge space (validated learning) (Hatchuel and Weil, 2003;Agogué and Kazakçi, 2014). (Agogué and Kazakçi, 2014) As visualized in Figure 1, the CK-Theory allows design explorations to different directions (C → C) and an advancement by logical reasoning within the knowledge space (K → K), but fosters reflection to the knowledge base (C → K) which again stimulates new design concept (K → C) propositions (Agogué and Kazakçi, 2014). By exploring new grounds, the CK-Theory supports the logic of set-based design in which a set of design concepts is developed further in parallel (Sobek et al, 1999).…”
Section: Ck-theory and Set-based Designmentioning
confidence: 99%